Ayurvedic concept of addiction, withdrawal & its solution - Porte, Sharad (International Journal of Pharmacology and Toxicology, 2014)
Background: Drug addiction is defined as the continued compulsive use of drugs despite adverse health or social consequences and Withdrawal is the physical and/or psychotic disorders developed by drug addicts after they stop taking drugs or reduce their dose. Drug addiction is very common in our society and it crosses all races, ethnic groups, and social classes. Methods: This research article is basis on personal experience & thorough review of Ayurvedic Text. The main Ayurvedic Text used in this study are Kashyapa, Charak, Sushrut, & Vangsen Samhita and available commentaries of those. Modern Texts & Article published in Journals also has referred to collect information on the relevant topics. Results: Ayurveda has mentioned the Alcoholism & Alcohol withdrawal under the heading of ‘Madatyaya & Panapakrama’ respectively. Ayurveda has mentioned the ‘Satmikarana’ a procedure of adaptation by gradual & logical decreasing the dose of addicted substance, which has already become a wholesome. Madya (Alcohol) in Madya is a unique principle which will be used in the treatment of addiction by decreasing the cellular level of drugs slowly & safe the patient from the withdrawal effect. The Padansha Krama which is described in the Ayurveda to reject the un-suitable substance will be necessary & useful to tapper up the addicted drugs. Psychological counselling, Recreational & Motivational Enhancement Therapy can be also used effectively for the rehabilitation the addicted patient, which is also described in Ayurveda. Conclusions: Thus Ayurveda have ultimate & effective solution in the Management & Rehabilitation of Drug Addiction. Keywords: Addiction, De-Addiction, Withdrawal Syndrome, Ayurvedic Solution.